CONTRIBUTIONS OF NATURAL RADIONUCLIDES IN CHEMICAL FERTILIZERS TO FARM SOIL RADIOACTIVITY AND COMMITTED EFFECTIVE DOSES TO HUMAN (2016)
The use of chemical fertilizers to replenish depleted soil nutrients due to over cultivation and erosion is a common practice. Natural radionuclides in these fertilizers can cause some radiological adverse health effects to animal, through indirect ingestion of fertilizer, including consumption of plants grown with fertilizers. Information on the level of contribution of chemical fertilizers to farm soil radioactivity and radiological health effects in Nigeria are scanty. This study was designed to assess the contributions of chemical fertilizers to farm soil radioactivity and Committed Effective Doses (CEDs) to human. Samples of commonly used Nitrogen-Phosphorus-Potassium (NPK:15-15-15) and Single Superphosphate (SSP) fertilizers were collected from retail markets in southern and northern Nigeria, respectively. Three partitions (0.55m2 each) of rain-fed experimental farm was filled with Virgin Soil (VS), which was collected from government reserved forest in Ekiti State. The fertilizers (NPK and SSP) were applied separately to VS with NPK (VSNPK) and VS with SSP (VSSSP) using broadcasting method at 1.0 kg/m2. The third partition served as the control (VSC). Seeds of Tomato (Solanum esculentum K. Karsten) and vegetable (Amaranthus hybridus Linnaeus) were sown on the partitions after one week of fertilizers application. The contributions of chemical fertilizers to farm soil radioactivity and their transfer factors to plants were investigated using standard method. The activity concentrations of natural radionuclides in the fertilizers, soil and plant samples were measured using Sodium Iodide doped with Thallium (NaI(Tl)) detector. The CEDs were determined using standard equation as contained in Radioactivity in Food and the Environment (RIFE) documents. Data were analysed using descriptive statistics and one way ANOVA at . The Mean Activity Concentrations (MACs) of in NPK and SSP were 4754.0±192.0, 156.0±99.0 and 9.4±4.0 Bq/kg; 301.0±36.0, 696.0±113.0 and 14.7±2.7 Bq/kg, respectively. The MACs of in soil samples of the were 204.0±2.4, 43.0±2.3 and 7.0±1.7 Bq/kg; 352.0±1.9, 62.0±1.7 and 8.0±1.9 Bq/kg; 285.0±3.3, 66.0±2.0 and 10.0±1.4 Bq/kg, respectively. The MACs of the three radionuclides in tomato samples of the VSC, VSNPK and VSSSP were 64.0±1.4, 18.0±1.7 and 7.0±1.7 Bq/kg; 125.0±2.1, 33.0±2.0 and 8.0±1.9 Bq/kg; 122.0±1.7, 51.0±1.4 and 10.0±1.4 Bq/kg, respectively were 72.0±1.4, 22.0±1.7 and 8.0±2.6 Bq/kg; 133.0±1.7, 45.0±1.9 and 10.0±1.9 Bq/kg; 142.0±2.3, 57.0±1.7 and 13.0±2.1 Bq/kg for respectively. Differences in MACs were significant in samples considered. Use of NPK and SSP contributed and respectively to the activity concentrations of in the VSNPK and VSSSP compared to the VSC farm soil. Radionuclide transfer factors in the VSC, VSNPK and VSSSP ranged from 0.36-0.66, 0.35-0.56 and 0.43-0.78, respectively. The CEDs due to consumption of tomatoes and vegetable of VSNPK and VSSSP were 0.22 and 0.11 and respectively, which are lower than the recommended CED of by International Commission on Radiological Protection (ICRP). The NPK and SSP fertilizers in the VSNPK and VSSSP contributed 54.0 and 130.0 %, respectively to the CED (tomatoes), 37.0 and 73.0 %, respectively to CED (vegetables) when compared to plants in the VSC. Chemical fertilizers contribute to farm soil radioactivity and the committed effective doses to human is elevated more by Single Superphosphate fertilizer